KEMAMPUAN MENALAR SILOGISTIK CALON GURU MATEMATIKA - SURYANTO, SURYANTO (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2015)
Abstract The objective of mathematics education covers the development of the students’ ability to use logical reasoning. At the Department of mathematics Education of IKIP Yogyakarta the sstudents study logic and set theory in the "Introduction to Foundations of Mathematics" (IFM) course. Categorical syllogism, shortened as syllogism, is an argument that is often used, but the subject matter of the IFM does not cover categorical syllogism. The problem is whether the course has developed the students’ ability in syllogistic reasoning. The study investigated the level of students’ ability in syllogistic reasoning and the correlation between the students’ grades in the IFM and the students’ ability in the syllogistic reasoning. The sample is 57 students who have taken the IFM at the Department of Mathematics Education. The ability in the syllogistic reasoning was measured by the a test on syllogism, where the students had to determine the validity of the 256 categorical syllogism in the standard form. Theresult indicates that the students’ ability in syllogistic reasoning is of low level and that there is no correlation between the students’ ability in syllogistic reasoning and the students’ learning achievement in the IFM (at the significance level of 0.05). therefore, it is recommended that the topic on categorical syllogism be included in the IFM course. Keywords: mathematics education, argument, categorical statement, syllogism, and syllogism reasoning.